Hidup ‘Uzlah (Mengasingkan Diri) Menurut Hadis Kitab Sunan Al-Nasa’i Nomor 2569 - Khozin, Muhammad; Jamaludin, Fitah; Afriza, Nugraha Andri (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2024)
Seclusion from the crowd of men or being alone and remembering Allah, and his deeds are solely for God. 'Uzlah is also a means that can bridge to get closer to Allah. 'Uzlah is done with the provision of knowledge, because 'uzlah that is not accompanied by knowledge is a great damage. Because 'uzlah must be understood first, then it can be 'uzlah. 'Uzlah is to seclude oneself from the crowd of people or to be alone and remember Allah, and to do one's deeds solely for Allah. 'Uzlah is also a means that can bridge to get closer to Allah. The focus of the research in this study is: 1) What is the quality of the hadith about 'uzlah (self-exile) in the book Sunan Al-Nasa'i number 2569?, 2) How is the contextualization of the hadith of 'uzlah (self-exile) in the present?. The objectives of this study are: 1) To find out the quality of the hadith about 'uzlah (self-exile) in the book Sunan Al-Nasa'i number 2569. 2) To find out the contextualization of the hadith of 'uzlah (self-exile) in the present. This type of research is qualitative research, the data collection technique used is library research with ma'anil hadith. The conclusions obtained are: 1) The hadith of 'uzlah (self-exile) in the book of Sunan Al-Nasa'i number 2569 is included in the degree of hadith shahih. 2) The hadith of 'uzlah (self-exile) in the present day can help human beings in keeping up with the erosion of the current of globalization and other worldly traits that sometimes make people neglect the rights that should be given to Allah. However, the way to do 'uzlah does not have to be done in a cave, a lonely place that is very far from human civilization, but it can be done in a lonely place that is not too far from humans. And the period of time used for 'uzlah does not need to be days, months or even years, but it provides free time that is felt to be enough to worship or get closer to Allah. On the other hand, in addition to getting closer to Allah, humans who practice 'uzlah can still socialize, stay in touch with other human beings, and be responsible for their families.